TINJAUAN HUKUM INTERNASIONAL TERHADAP KETEGANGAN ANTARA IRAN DAN PAKISTAN - Suryani, Nani; Oktafiani, Dwi Putri (Bhinneka Multidisiplin Journal, 2024)
Recent political tensions between Iran and Pakistan have heated up quite a lot after Iran accidentally fired a missile into Pakistani territory and received a response from Pakistan. Although Iran has said that the attack was aimed at the separatist movement inhabiting the Iran-Pakistan border region, civilians from both sides were also victims of the incident. This research discusses the issue of how International Criminal Law views these tense incidents. This research uses a descriptive qualitative approach and data collection techniques, namely literature study. Iran-Pakistan tensions are indeed an international crime committed by their respective governments, because they include the freedom of civil society living in border areas. However, this case cannot be submitted to the International Court of Justice because both countries have agreed not to file charges. Apart from that, separatist movements carried out by Iranian and Pakistani separatist groups can also be categorized as international crimes because they create threats to the security of citizens of these two countries